Electrocorticographic(ECoG) monitoring in spontaneous intracerebral hemorrhage(sICH): Metabolic profile of cortical spreading depolarizations(CSD). Issue 3 (March 2016) - Fabricius, M.; Schiefecker, A.J.; Friberg, C.K.; Beer, R.; Pfausler, B.; Lackner, P.; Broessner, G.; Sohm, F.; Mulino, M.; Thome, C.; Schmutzhard, E.; Helbok, R.
Abstract : Objective: Metabolic changes accompany CSDs in clinical secondary brain injury. This was investigated for the first time after sICH. Methods: Patients with sICH were enrolled in COSBID (Co-operative Study on Brain Injury Depolarisations). Prolonged depressions of ECoG was used to detect CSDs. Brain tissue oxygen tension (PbtO2), cerebral blood flow (CBF), and cerebral metabolism (microdialysis) were monitored in the region of perihematomal edema (PHE). Results: 18 patients (38% female, 55–67 years) had an ICH volume of 33–69 ml. Hematoma evacuation ( n  = 17) or craniectomy only ( n  = 1) was performed. During monitoring for 10 (6–14) days, a total of 129 CSDs were observed in 66.7% ( n  = 12) of patients. CSDs occurred in 73% ( N  = 11) of patients with PHE expansion. CSDs were directly associated with a significant decrease of PbtO2 (−4mmHg [−3;−7]) in 68% (52/77), CBF changes in 95% (19/20), and metabolic derangement in 80% (80/100) of events. PHE expansion was observed in all patients with spreading convulsions ( N  = 2) and patients with repetitive CSDs. Conclusions: CSDs are associated with local PbtO2 decreases. Clusters of CSDs in particular seems to be associated with detrimental metabolic changes of the perihematomal brain tissue. Key Message: ECoG reveals brain pathophysiology of sICH: CSDs are frequent and accompanied by metabolic derangement.